PEMANFAATAN DANA DESA DITINJAU DARI ASAS TRANSPARANSI DI DESA WONOREJO KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Indhiraputra, Evan Nandihika; Suranto, Suranto (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This study aims to find out how the utility of village fund reviewed by good government principles in Wonorejo Village, Gondangrejo distrct, Karanganyar Regency and obstruction in utilization village fund.The kind of research used in this research is a empirical and descriptive legal research. The type of used data is primary data and secondary data. The source of primary data  is direct interview  with related parties of the research. The sources of secondary data are literature, regulations, journals, articles and materials from the internet and other related sources. Technique of data collection that be used are field studies which directed to the object of research and literature study to obtain theoretical basis related to the research.Based the result of the research and discussion, Utilization of Wonorejo Village Fund, Gondangrejo district, Karanganyar Regency apply transparency principle. The planning phase of the use of village funds is done by involving the people who are members of the musrenbangdes to ensure the openness of the Village Government at an early stage. The management phase is carried out by installing a detailed development budget board from the village fund, and at the accountability monitoring stage, the development completion report by the village head and village officials invites BPD, LPMD and community leaders once every three months to evaluate the implementation of the Village Fund program that has been done. Wonorejo village experienced difficulties in managing village funds, not maximizing the use of village funds for development, late disbursement of village funds from central and local government, lack of village government knowledge on accountability reporting, and numerous regulations on village funds.